Implementation of Wasathiyah Concept for Virtual Communities - Lubis, Nurfauzy (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This study discusses how the concept of wasathiyah in Surah Al Baqarah 143 is applied in the digitalization era. In some ways, the changes that have occurred are not accompanied by human readiness as social media users. So various problems of religious moderation arise on social media such as shifts in religious authority, distorted understanding of religion, and abnormal behavior of social media users towards religious issues. For this reason, it is necessary to explain the concept of washatiyah in the Qur'an as a digital literacy guide for virtual communities in the era of society 5.0 to shape the moderate behavior of social media users. Various previous studies have discussed religious moderation in a normative-traditional context. Therefore it is necessary to apply the wastathiyah which applies to virtual space in this digitalization era. This study uses library data collection, in the form of books and interpretations of verses of the Qur'an, especially surah Al Baqarah verse 143. The results of the study show that first, moderate behavior in surah Al Baqarah 143 tawassuth ,bawazun ,and tasamuh. Second, the principle of fairness in commenting on social media must be applied. Third, moderation can be implemented by filtering information before commenting.